The dynamic relationship between health care expenditure and national income in Benin context - HOUENINVO, GBODJA HILAIRE (My University, 2023)
: This paper provides empirical evidence on the relationship between per capita health care expenditure and national income in Benin, over the period from 1990 to 2020, using AutoRegressive Distributed Lag (ARDL) approach. After controlling for domestic government health expenditure as share of total health expenditure, foreign health expenditure as share of total health expenditure, proportion of population aged less than 15 years old and proportion of population aged over 65 years, we found that the long-run elasticity of health care with respect to gross domestic product is ranged from 0.529 to 0.676 suggesting that health care is income inelastic for Benin’s citizens. Our results remain stable when re-estimating the same health expenditure equation by Fully Modified Ordinary Least Squares and Dynamic Ordinary Least Squares methods. Since income elasticity of demand for health care expenditure is less than one, higher income may not automatically imply higher health expenditure by Benin population.
Keywords: Health care expenditure – Bound testing – Heath financing – Benin